Targeting reasoning biases in delusions: a pilot study of the Maudsley Review Training Programme for individuals with persistent, high conviction delusions. - Waller, H; Freeman, D; Jolley, S; Dunn, G; Garety, P (Elsevier, 2011)
Delusions are often resistant to change, persisting despite successful antipsychotic treatment or Cognitive Behavioural Therapy. This study aimed to target reasoning processes, particularly the 'Jumping to Conclusions' (JTC) bias and belief flexibility, which are thought to play a part in maintaining delusional conviction. 13 participants with a diagnosis of psychosis and high levels of conviction in their delusions completed a one-off computerised training package, lasting approximately 1.5 h. Outcomes were assessed at baseline, pre-intervention (two weeks later), post-intervention (immediately after completing the training) and at 1 month follow-up. The package was well received by participants. There were improvements in JTC, belief flexibility and delusional conviction between pre- and post-intervention measures. Controlled studies powered to detect changes in key outcomes are warranted in order to evaluate the efficacy of the programme.